2016
DOI: 10.1080/02705060.2016.1160846
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of algal communities in small streams and ditches in temperate regions using delayed fluorescence

Abstract: Because of their high ecological relevance, algae are often used in environmental monitoring of freshwater ecosystems. They are used to assess the state of the environment, and can be used to estimate the diversity and productivity of the ecosystem. Chlorophyll a is the most commonly used indicator where no taxonomic information is obtained. In this two-year study, algae were monitored in small lotic waterbodies using a high precision method of evaluating algal pigments: delayed fluorescence (DF). The method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The sampling sites were in three streams, Klein (K1, K2, K3), Haverbach (H) and Rulfbach (R1, R2), and two ditches, Ditch A (A1, A2) and Ditch B (B1, B2; Figure 1). A detailed description of the waterbodies is provided by Breuer et al (2016). No lentic waterbodies were connected to the investigated streams and ditches.…”
Section: Study Area and Sampling Sitesmentioning
confidence: 99%
“…The sampling sites were in three streams, Klein (K1, K2, K3), Haverbach (H) and Rulfbach (R1, R2), and two ditches, Ditch A (A1, A2) and Ditch B (B1, B2; Figure 1). A detailed description of the waterbodies is provided by Breuer et al (2016). No lentic waterbodies were connected to the investigated streams and ditches.…”
Section: Study Area and Sampling Sitesmentioning
confidence: 99%
“…Although irradiance regimes affect both suspended and attached phototrophs in flowing waters (Munn et al 1989; Hutchins et al 2010), effects of photon flux vary seasonally with discharge and turbidity (Biggs 1995; Leland 2003), canopy cover (Rosemond et al 2000), nutrient content (Glibert et al 2016), and temperature (Baker and Baker 1979; Munn et al 2002; Wu et al 2011). Such seasonal changes also drive patterns of benthic and suspended community development (Andrus et al 2015), with enhanced production of diatoms in spring and fall and elevated densities of chlorophytes and cyanobacteria in summer (Breuer et al 2016; Moorhouse et al 2018). Overall, the degree to which natural phototrophic phenology interacts with effluent influx is poorly understood (del Giorgio et al 1991; Stevenson and White 1995; Solomon et al 2019), particularly for streams in nonboreal systems such as agricultural grasslands (Dodds et al 2004; Breuer et al 2017).…”
mentioning
confidence: 99%
“…Phototrophic communities were quantified using taxonomically diagnostic pigment biomarkers (chlorophylls [Chl], carotenoids) to measure: (1) how regional variation in physico‐chemical conditions affected development of phototrophic biomass and community composition; (2) how modern effluent affected phytoplankton and periphyton; and (3) whether urban effluent had a differential effect on suspended or attached communities. We hypothesized that: (1) landscape patterns of abundance, composition and interaction of phytoplankton and periphyton would reflect spatial and temporal variation in regulation by physico‐chemical parameters (discharge, irradiance, temperature) in these eutrophic streams (Breuer et al 2016, 2017; Moorhouse et al 2018); (2) effluent influx would overwhelm natural landscape controls (discharge, irradiance, temperature) of periphyton (Murdock et al 2004; Hamdhani et al 2020) and phytoplankton development (del Giorgio et al 1991; Stevenson and White 1995; Solomon et al 2019); (3) modern urban effluent would favor phytoplankton over periphyton due to both changes in nutrient (Chambers et al 2012; Dodds and Smith 2017) and irradiance regimes (Munn et al 1989; Rosemond et al 2000); and (4) NO 3 − from effluent would favor siliceous algae and chlorophytes over cyanobacteria downstream of wastewater treatment plant outfall (Glibert et al 2016; Swarbrick et al 2019).…”
mentioning
confidence: 99%
“…Delayed fluorescence excitation spectroscopy, a high precision method of measuring photosynthetically active pigments (the composition of which differ in different algal groups) via excitation of algal cells by monochromatic light, correlated strongly with algal biovolume and composition from cell count data and may be used in monitoring of algal biomass (Breuer et al, 2016). A test of the fluormetric probe, BenthoTorch, to rapidly assess toxinproducing algal assemblages like Phormidium, found that chlorophyll a measurements correlated well with thin mats (< 2 mm) and mats < 50% cyanobacteria by biomass, but not more, which may be due to underestimation of phycoerythrin and limitations of the probe to measure the upper layers of biofilms (Echenique-Subiabre et al, 2016).…”
Section: Methodsmentioning
confidence: 99%